Prevalence of high-risk human papilloma virus infection and cervical cytological abnormalities in female Turkish patients with rheumatologic disease - Yalçınkaya, Cem; Kale, İbrahim; Pehlivan, Özlem (Journal of Surgery and Medicine, 2022)
Background/Aim: It is believed that patients with rheumatological diseases (RDs) are more prone to infectious diseases, possibly due to both disease-related immune dysfunction and chronic inflammation, and immunosuppressive agents used in the treatment of rheumatological diseases. In this context, we aimed to evaluate the prevalence of high-risk human papillomavirus (Hr-HPV) infection and cervical cytological abnormalities in Turkish female patients with RDs and compare them with healthy controls (HCs). Methods: 362 sexually active patients with RDs followed up between January 2014 and June 2021 were included in this cross-sectional study. Patients with RDs were classified as autoimmune and non-autoimmune groups according to seropositivity. Data of 883 age-matched HCs were used for comparison. Demographic features, cervical cytology reports of the patients and HPV test results were retrieved from hospital database. Cervical cytological abnormalities was categorized according to Bethesda 2014. Cobas assay was used for detecting and typing for Hr-HPV. Results: The RDs group and the HCs group were similar in terms of mean age, BMI, and rate of smokers (P>0.05). Cytological evaluation was carried out in all of 362 patients with RDs (161 autoimmune and 201 non-autoimmune) and in all of 883 HCs. HPV test was applied in 286 patients with RDs and 776 of HCs. 16 (4.4%) patients with RDs and 58 (6.6%) HCs had cervical cytological abnormality. Of the patients who underwent HPV testing; 22 (7.7%) patients with RDs and 75 (9.7%) HCs had Hr-HPV. The prevalence of cervical cytologic abnormalities and Hr-HPV infection rate were similar between patient groups and HCs (P=0.186 and P=0.400, respectively). Conclusion: It was determined that chronic systemic inflammation, which plays a role in the pathogenesis of rheumatological diseases, and immunosuppressive agents used in the treatment did not increase the prevalence of Hr-HPV infection and cervical cytological abnormalities.